Atypical Sarcoidosis Diagnosed by Massive Splenomegaly - Saito, Satomi (Intern Med, 2019)
We examined a 22-year-old woman who was admitted to our hospital with abdominal distention. At 19 years of age, the patient presented with hepatosplenomegaly. She was examined several times in another hospital; however, the cause was unidentified. Our evaluation showed severe pancytopenia and a spleen 13×24 cm in size. The serum levels of angiotensin-converting enzyme and lysozyme were elevated. She was diagnosed with liver sarcoidosis based on non-caseating epithelioid granuloma in liver biopsy tissue. To improve the symptoms, splenectomy was performed, and her pancytopenia and symptoms improved. Sarcoidosis should be considered in cases of massive splenomegaly.